Manifestation of Contemporary Leadership Issues and its Relevance to Diverse Leadership Methods and Contingency Models: A Review of Literature (Global Journal of Human-Social Science, 2013)
explains that, "leadership remains an ambiguous, amorphous, and frequently misunderstood topic" (p. ix). Therefore, isolating and discussing a limited number of leadership models may suggest one is more significant than the other. This paper purposefully lacks the attachment of special significance, and instead, offers a limited focus on certain contingency theories. The present paper reviews the literature of studies conducted by using diverse leadership methods, the similarities and differences in these leadership models.
Keywords: diverse; leadership methods; transactional; transformational; situational; charismatic